Shrek - Adamson, Andrew; Jenson, Vicky; Elliott, Ted, 1961-; Steig, William, 1907-2003; DreamWorks Pictures (1994-2006) (Madrid : DreamWorks Home Entertainment ; Twentieth Century Fox Home Entertainment, 2009)
In a faraway land called Duloc, a heartless ruler, the midget Lord Farquaad has banished all the fairy tales from the land so it can be as boring as he is. But there are three characters who will stand in his way. The first is a green, smelly ogre with a heart of gold named Shrek, his faithful steed, a donkey, who will do anything but shut up, and the beautiful, but tough Princess Fiona whom Lord Farquaad wishes to make his wife so he can become king of Duloc.
Special features: Dubbing studio -- Interactive games -- Interviews -- The artistic staff -- The technology of Shrek -- International dubbing -- Shrek in the swamp dance with karaoke -- Animated menus -- Filmographies.
Originally released as a motion picture in 2001.
Based on the book by William Steig.
Executive producer, Penney Finkelman Cox ; editor, Sim Evan-Jones; music, Harry Gregson-Williams, John Powell.
Voices : Mike Myers, Eddie Murphy, Cameron Diaz.
General audience.
DVD, region 2; widescreen, aspect ratio 1.78:1; Dolby digital 5.1.
Keywords: Ghouls and ogres -- Drama; Ugliness -- Drama; Computer animation films; Feature films; Fiction films